The Mediating Role of Perceived Value in the Relationship Between Service Quality and Customer Satisfaction: Evidence from a Tourism Souvenir Store in Garut Regency - Sani Vira Febriani; Dini Turipanam Alamanda; Wufron Wufron (International Journal of Management Science and Information Technology, 2026)
In tourism-related retail, customer satisfaction is a critical determinant of business competitiveness and sustainability. Souvenir stores are particularly vulnerable to fluctuations in tourist arrivals, which may affect service quality during peak demand periods. This study examines the effect of service quality on customer satisfaction and investigates the mediating role of perceived value. The research was conducted at “S” Souvenir Store in Garut Regency, Indonesia, a tourist destination characterized by seasonal visitor fluctuations. An explanatory quantitative approach was employed, with data collected from 110 customers through a structured questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that service quality has a significant positive effect on both perceived value and customer satisfaction. In addition, perceived value has a significant positive effect on customer satisfaction and partially mediates the relationship between service quality and customer satisfaction. These findings suggest that customer satisfaction is influenced not only by service performance but also by the perceived value derived from the exchange. Theoretically, this study contributes to tourism retail literature by positioning perceived value as a mediating mechanism in the relationship between service quality and customer satisfaction. Practically, souvenir retailers should focus not only on improving service delivery but also on enhancing customers’ perceived value to strengthen satisfaction outcomes.